If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3Xsquared + 5X + 7 = 0 Reorder the terms: 7 + 5X + 3adeqrsuX = 0 Solving 7 + 5X + 3adeqrsuX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 5X + -7 + 3adeqrsuX = 0 + -7 Reorder the terms: 7 + -7 + 5X + 3adeqrsuX = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 5X + 3adeqrsuX = 0 + -7 5X + 3adeqrsuX = 0 + -7 Combine like terms: 0 + -7 = -7 5X + 3adeqrsuX = -7 Reorder the terms: 7 + 5X + 3adeqrsuX = -7 + 7 Combine like terms: -7 + 7 = 0 7 + 5X + 3adeqrsuX = 0 The solution to this equation could not be determined.
| -8/3=-15/n | | 2x^3y-8x^2y^2-6xy= | | -24+3n=8(-7n-3) | | 3x(x-1)=(3x-6)(x+1) | | 1/15(15) | | 74=1.8x+32 | | 41-28= | | 2(-7x-9)=2(1-9x) | | -6(-x+8)=-6x+12 | | ((x^2+1)/(x^2-1))/((x+1)/(x-1)) | | 6t-12=18t-4 | | B(5px-3c)=a(9x-4) | | (-4)-47= | | -8/3=-15-n | | 21/6x=51/5 | | a^2+7a=-10 | | 6x+2=3(3+2x) | | 17y=-13 | | 7.6x-4.9x=-43.2 | | 12.5=-43.2 | | (.5)(12-6x)=4-2x | | 5/11-2/11 | | 2m^2+3=3 | | (-12)(11)= | | 5x-8=3x-28 | | 12.5x=43.2 | | 1/3(12x+9)=11-5(x-3) | | -0.8n=4 | | 15x=-90 | | -8(2x-1)=-5(2x+8) | | -6x-2=100 | | 5(2x-4)=3(4x+12) |